Effects of an adapted crossfit program combined with nutritional counseling on adiposity indicators, muscular fitness and functionality of young people with intellectual disabilities - Ubilla-Mejias, Melissa; Espoz-Lazo, Sebastián; Valdivia-Moral, Pedro; Piñeiro-Cossio, Javier; Castillo-Paredes, Antonio; del Val-Martín, Pablo; Andrades-Ramirez, Oscar; Peña- Baeza, Alonso; Farias-Valenzuela, Claudio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to determine the effects of a combined adapted CrossFit® training program and nutritional counseling on indicators of adiposity, muscular fitness and functionality of school-age adolescents with intellectual disabilities. The sample was made up of (n=11) subjects belonging to the work level of a special education center in Santiago de Chile. Anthropometric measurements of adiposity, muscle strength, and functional capacity were performed before and after a combined 15-week adapted Crossfit® training and nutritional counseling program. Significant changes were observed in adiposity indicators such as the waist-height ratio (Δ% = -6.12), in the landing force in the countermovement jump (Δ% = -18.34) and in the 5-hour functional tests. repetitions of getting up and sitting down. down from a chair (Δ% = -8.16), Timed up and go (Δ% = -8.15), Countermovement jump (Δ% = -8.36) and in the 4 x 10 m Agility test (Δ% = -8.00). In conclusion, a 15-week combined training program of adapted CrossFit® and nutritional counseling had positive effects on indicators of adiposity, muscular fitness and functionality in a sample of school-aged adolescents with intellectual disabilities. This intervention strategy is safe and can be used to promote the practice of physical exercise and healthy lifestyles from special educational establishments.